2008
DOI: 10.1002/biof.5520320124
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of coenzyme Q10 (CoQ10)

Abstract: Coenzyme Q10 (CoQ10) is a naturally occurring component present in living cells. Its physiological function is to act as an essential cofactor for ATP production, and to perform important antioxidant activities in the body. In most countries, CoQ10 has been widely used as a dietary supplement for more than 20 years. Recently, the use of CoQ10 as a dietary supplement has grown with a corresponding increase in daily dosage. The present review describes the safety profile of CoQ10 on the basis of animal and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
113
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(125 citation statements)
references
References 40 publications
1
113
0
11
Order By: Relevance
“…This concentration was consistent with previous report on in vivo CoQ 10 testing Cleren et al, 2008) as well as with CoQ 10 dosing of PD patients in clinical trial (Shults et al, , 2002. However, although at this concentration Ubisol-Q 10 was well tolerated, the delivered dose of CoQ 10 was well above the acceptable daily intake (ADI) of 12 mg/kg/day (Hidaka et al, 2008). Therefore, in the next set of experiments, we proceeded to test Ubisol-Q 10 at 5× and 10× lower doses, that is, 6 mg/kg/day and 3 mg/kg/day, well within the ADI value.…”
Section: Therapeutic Neuroprotection Could Be Achieved At Much Lower mentioning
confidence: 99%
“…This concentration was consistent with previous report on in vivo CoQ 10 testing Cleren et al, 2008) as well as with CoQ 10 dosing of PD patients in clinical trial (Shults et al, , 2002. However, although at this concentration Ubisol-Q 10 was well tolerated, the delivered dose of CoQ 10 was well above the acceptable daily intake (ADI) of 12 mg/kg/day (Hidaka et al, 2008). Therefore, in the next set of experiments, we proceeded to test Ubisol-Q 10 at 5× and 10× lower doses, that is, 6 mg/kg/day and 3 mg/kg/day, well within the ADI value.…”
Section: Therapeutic Neuroprotection Could Be Achieved At Much Lower mentioning
confidence: 99%
“…CoQ 10 is widely recognised as safe with no reported toxicity (123) . It has been shown that CoQ 10 supplementation (100 mg/d) in HC patients treated with atorvastatin (10 mg/d) did not have an effect on statin-induced reductions in total or LDL-cholesterol, or TAG levels (124) .…”
Section: Safety Aspects Of Combination Therapy With Coenzyme Q 10 Andmentioning
confidence: 99%
“…2) In 1961, the important role of CoQ 10 as an electron carrier in the electron transport pathway was first proposed by Peter Mitchell, making it a subject of interest to medical and pharmaceutical researchers. 3) Since then, substantial amounts of laboratory and animal data on CoQ 10 have been published.…”
mentioning
confidence: 99%
“…3) Since then, substantial amounts of laboratory and animal data on CoQ 10 have been published. These findings indicate that, in addition to its function as an electron carrier, CoQ 10 acts as an antioxidant and can prevent damage to cellular components caused by free radicals and can also stabilize cell membranes.…”
mentioning
confidence: 99%